2023
DOI: 10.1002/csc2.20971
|View full text |Cite
|
Sign up to set email alerts
|

Agro‐morphological characterization and diversity analysis of Coffea arabica germplasm collection from INIA, Peru

Abstract: Coffee (Coffea arabica L.) plays a major role in the economy of Peru and the world. The present study aims to elucidate the agro‐morphological variability of coffee genotypes maintained in the National Institute of Agrarian Innovation (INIA) germplasm collection. Therefore, 20 vegetative, reproductive, and phytosanitary traits of 162 coffee accessions of INIA's germplasm collection were evaluated and analyzed. Correlation results indicate that a simultaneous selection of characters, such as number of branches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…These studies also focus on determining the genetic diversity of H. vastatrix and its distribution area (Gamarra et al, 2021;Quispe-Apaza et al, 2021;Le et al, 2022;Ramírez-Camejo et al, 2022). Studies have also been reported where genotypes of interest are evaluated under greenhouse conditions using a H. vastatrix uredospore suspension obtained from infected coffee leaves of plants in field (Bustamante et al, 2001;Paredes-Espinosa et al, 2023). Currently, optimal conditions of temperature, humidity, light intensity, and photoperiod can be simulated under laboratory conditions using specialized equipment, such as phytotrons, which are climatic chambers designed for plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also focus on determining the genetic diversity of H. vastatrix and its distribution area (Gamarra et al, 2021;Quispe-Apaza et al, 2021;Le et al, 2022;Ramírez-Camejo et al, 2022). Studies have also been reported where genotypes of interest are evaluated under greenhouse conditions using a H. vastatrix uredospore suspension obtained from infected coffee leaves of plants in field (Bustamante et al, 2001;Paredes-Espinosa et al, 2023). Currently, optimal conditions of temperature, humidity, light intensity, and photoperiod can be simulated under laboratory conditions using specialized equipment, such as phytotrons, which are climatic chambers designed for plant growth.…”
Section: Introductionmentioning
confidence: 99%